Blockchain Implementation for Data Security in Digital Food Courts: Examining Socio-Economic and Environmental Impacts in the Case of Kestalan’s Digital Transformation - Ekowati, Maria Atik Sunarti; Wening , Sri; Rumekso , Ayub Widhi (Asian Journal of Environmental Research, 2024)
Blockchain technology has emerged as a transformative solution for enhancing data security in various sectors, including retail sales operations. This study explores its implementation in flexible food courts as part of digital transformation initiatives, focusing on bolstering data security, improving transparency, and streamlining sales processes. Blockchain's decentralized, immutable, and encrypted ledger addresses issues like data manipulation, fraud, and cybersecurity risks, making it particularly suitable for food courts adopting digital payment systems. Using a descriptive case study approach, the research employs interviews, direct observation, and literature reviews to examine blockchain's role in managing digital transactions, cashless payments, and real-time inventory tracking. The findings reveal that blockchain enhances data security by preventing unauthorized access, expediting transactions, and fostering customer trust through transparent, tamper-proof records. It also reduces operational inefficiencies and costs associated with data management and fraud prevention. However, challenges such as high implementation costs and a steep learning curve hinder widespread adoption. Despite these barriers, blockchain provides a robust framework for supporting digital transformation in flexible food courts, particularly among small and medium enterprises (SMEs), by ensuring secure, efficient, and transparent data management. The study recommends developing simpler, more affordable blockchain solutions tailored to SMEs and offering user training programs to facilitate smoother adoption. These advancements could pave the way for broader implementation, enhancing operational efficiency and fostering trust in digital ecosystems.